Dear Peter Rabbit - Ada, Alma Flor.; Tryon, Leslie (New York : Scholastic Inc, 1994)
Presents letters between such fairy tale characters as Goldilocks, Baby Bear, Peter Rabbit, and the Three Pigs.
G5
Keywords: Characters in literature -- Fiction; Letters -- Fiction